Monitoring and modelling of butyltin compounds in Finnish inland lake - Ahkola, Heidi; Juntunen, Janne; Krogerus, Kirsti; Huttula, Timo (Frontiers in Environmental Chemistry, 2022)
In this study we measured the total concentration of BTCs using grab water sampling, dissolved concentration with passive samplers, and particle-bound fraction with sedimentation traps in a Finnish inland lake. The sampling was conducted from May to September over two study years. In grab water samples the average concentration of MBT at sampling sites varied between 4.8-13 ng L-1, DBT 0.9-2.4 ng L-1, and TBT 0.4-0.8 ng L-1 during the first study year and 0.6-1.1 ng L-1, DBT 0.5-2.2 ng L-1 and TBT